ANALISIS MUTU PRODUK ROTI MAROS SANGGALEA GROUP MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT - Herdianzah, Yan; Mubaraq, Husni; Nusran, Muhammad; Ahmad, Arfandi; Safutra, Nur Ihwan; Fole, Asrul (Universitas Putera Batam, 2024)
Bread is a processed food made from wheat flour which is considered practical and filling. Roti Maros Sanggalea Group, Roti Maros Sanggalea Group is a trading business with processed products in the form of wet bread. The type of moist bread that is the flagship of Roti Maros Sanggalea Group is Maros bread. However, there has been a decline in demand for Maros bread over the past year. This decline can be seen in Maros bread production for the period January to March 2023. The decline in sales each month requires producers to develop their products well so they can always compete in the market. Therefore, this research aims to provide suggestions for attributes that consumers prioritize for Maros Sanggalea Group Roti products using the QFD (Quality Function Deployment) method to improve the quality of Maros bakery products by identifying consumer needs and linking them to improvements in production techniques. The research results show that based on the priority level, the proposed improvement is by completing information about the product on the packaging, as well as adding a halal logo to the packaging, the price given to consumers must be in accordance with the quality of the product both in terms of ingredients and taste. Make the products being marketed easy for consumers to remember, for example uniquely designed packaging or distinctive flavors.